Evaluación de la bioseguridad en una granja avícola de la provincia de Santa Elena, Ecuador (2021)
Foodborne illness is a major health problem. global public health due to its magnitude, socioeconomic impact and the emergence of emerging pathogens. It is estimated that between 15% and 20% of these diseases are directly associated with the consumption of chicken meat or its derivatives. Therefore, the food chain, especially in its primary phase, has played a predominant role in increasing the epidemiological risk of diseases transmitted by food and in the dissemination of resistance genes in the population bacterial.